Editorial: application of ultraviolet light to air, water, and wastewater treatment. Issue 3 (1st May 2007) - Bolton, James R; Smith, Daniel W; Craik, S A
Abstract : This is a special issue of the Journal of Environmental Engineering and Science dedicated to applications of ultraviolet (UV) technologies. Since the first UV supplement was published in 2005, there have been a number of developments related to the application of UV in water and wastewater and the engineering science has developed rapidly. The articles in this issue capture a portion of that activity.